Clinical characteristics of patients with undergoing unplanned excisions of malignant soft tissue tumors. (3rd November 2021) - Morinaga, Sei; Miwa, Shinji; Yamamoto, Norio; Hayashi, Katsuhiro; Takeuchi, Akihiko; Igarashi, Kentaro; Tada, Kaoru; Langit, Mickhael B; Yonezawa, Hirotaka; Araki, Yoshihiro; Asano, Yohei; Tsuchiya, Hiroyuki
Introduction: Malignant soft tissue tumors are rare tumors representing <1% of all malignancies. As these tumors are rare, it is not uncommon that malignant soft tissue tumor excision is performed without the required preoperative imaging, staging, or wide resection margins for sarcomas. The purpose of this study was to investigate the characteristics of patients with undergoing unplanned excisions. Risk factors for tumor recurrence and mortality in patients treated with unplanned excisions were also analyzed. Methods: Forty-nine patients who underwent unplanned excision at other hospitals and additional wide excision at our hospital between January 2002 and December 2018 were identified. Among them, 42 patients with follow-up for more than 1 year were included in this retrospective study. The relationships between sex, age, tumor depth, histological grade, location, size, surgical margin at additional wide excision, residual tumor, reconstruction, kind of hospital where the primary excision was done (sarcoma vs non-sarcoma center), preoperative examination, chemotherapy, radiation therapy, and oncological outcomes were statistically analyzed. Results: Mean patient age was 57.3 years (15–85 years) and the mean observation period was 72.5 months (14–181 months). This analysis showed 53.8% tumors that underwent unplanned excisions were small (<5 cm) and 70.7% tumors were superficial. Multivariate analysis revealed that a positive margin during additional wide excision was significantly associated with a lower 5-year LRFS ( p < 0.01). Conclusion: Most of the tumors underwent unplanned excisions were small (<5 cm) and superficial. Surgeons should be aware that a positive margin during additional wide excision is an independent risk factor for local recurrence.